AN OVERVIEW OF TRADITIONAL KANCHIPURAM SILK SAREES - Keerthi, Nellutla; E, Mokanaa Sri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kanchipuram Silk Sarees are among the most desired traditional wear for the ever-bothersome question of elegance and prestige of culture, as well as for the legendary history of this district and the brilliantly exclusive craftsmanship combining this textile. South Indian bridal culture has existed for ages, and the Kanchipuram silk saree has been a ruling trend among more sophisticated ladies for a long time. The charming silk sarees, designed individually with gold or silver zari and pure silk threads, from Kanchipuram, a town in Tamil Nadu, are examples of the textile industry’s brilliant creations. Kanchipuram Silk Sarees are a paragon of taste and history for their intricate craftsmanship that depicts their exclusive weaving styles, choice of luxury materials, and everlasting patterns. These sarees convey the rich textile legacy of our country and mesmerise worldwide fashion enthusiasts with their extraordinary combination of culture and modernity. They are still worn as a form of importance during events and passed down as family heirlooms because they are truly outstanding pieces. This paper covered the historical value, manufacturing methods, current trends, market identification, and cultural importance of Kanchipuram silk sarees in contemporary times. It also thoroughly describes the features and their still-thriving cognizance today in eastern Indian fabrics. In addition, the SWOT analysis included in this study highlights the strengths, weaknesses, opportunities, and threats associated with the Kanchipuram silk industry. Elements of the fabric, including durability and brilliance, as well as intricate patterns and motifs, are the main selling points for maintaining its rich cultural legacy.